AGING, GENDER AND CARE: EDUCATIONAL PROCESSES IN THE CARE OF THE ELDERLY - Aline Ferreira Brito Rodrigues, Beatriz; Tiago da Silva Alves, Emerson; Lorena Souza Silva, Mariane; Santos Santana, Eric; Andreza de Arruda, Marília; Dayze de Carvalho Souza, Jordana; Regina Costa Moreira, Sabrina; Sales de Medeiros, Fransueide; Cristiane de Oliveira Onibeni, Denise; Nelson Martins Júnior, Leonidas (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to analyze educational processes focused on the care of older adults, emphasizing the intersections between aging, gender, and care, based on a narrative literature review. The research included eight published studies, selected based on their theoretical and empirical relevance. Data analysis identified two central thematic categories: (1) health education as a strategy for promoting active and participatory aging; and (2) gender inequalities and invisibilities that particularly impact older women in care settings. The results show that educational practices grounded in dialogue, intergenerationality, and the valuing of popular knowledge contribute to the autonomy and protagonism of older adults. At the same time, they point to the urgent need for public policies sensitive to gender issues and diversity in old age. It concludes that educational processes are powerful tools for building more equitable, humanized, and inclusive healthcare for the older population.